2018
DOI: 10.1016/j.ultsonch.2017.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Low frequency ultrasound pretreatment of carrot slices: Effect on the moisture migration and quality attributes by intermediate-wave infrared radiation drying

Abstract: The effect of low frequency ultrasound (LFU) pretreatment prior to intermediate-wave infrared radiation (IW-IR) drying on water migration and quality attributes of carrot slices was investigated in this study. Results showed that the vacuole water of LFU pretreated carrot samples decreased, while the cytoplasm and intercellular space water increased by low-field nuclear magnetic resonance analysis. In addition, LFU pretreatment caused the disruption of cell structures and formation of micro-channels, resulting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
85
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 210 publications
(95 citation statements)
references
References 40 publications
9
85
0
1
Order By: Relevance
“…() used the Weibull model to describe the drying behavior of red bell pepper and established that the R 2 was greater than 0.99, chi‐square values were below 0.001, and with the least RMSE. These results are in agreement with what has been previously reported by other researchers for red bell pepper (Wang et al., ) and cucumber (Kiani et al., ).…”
Section: Resultssupporting
confidence: 94%
“…() used the Weibull model to describe the drying behavior of red bell pepper and established that the R 2 was greater than 0.99, chi‐square values were below 0.001, and with the least RMSE. These results are in agreement with what has been previously reported by other researchers for red bell pepper (Wang et al., ) and cucumber (Kiani et al., ).…”
Section: Resultssupporting
confidence: 94%
“…In the current study, the increase in SG with high PT and low UF (Figure e) can be attributed to the ultrasonic cavitation, which permeated the cell membrane and enhance the mass transfer of water and solid from the ginger sample. This result is consistent with the findings of Wang et al (), who revealed that low application of US frequency enhanced SG of carrot sample. The quadratic model that depicts the link between SG and the OS parameters are below (Final Equation in Terms of Coded Factors): Solid Gain()%=12.674.95X1+1.10X2+0.30X30.62X1X20.21X1X37.50×103X2X30.78X12+0.23X22+0.37X32. …”
Section: Resultssupporting
confidence: 93%
“…The RR was measured according to Wang, Xu, Wei, and Zeng () in Equation 6: 1.25emRR=W1/W2 where W 1 (weights of the samples before rehydration) and W 2 (weights of the samples after rehydration) were measured, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, the authors proposed that this could be interesting for the preservation of phenolic compounds and the antioxidant activity when high‐density US and lower drying temperature are applied. Wang et al ., also showed that the application of US enhanced the convective drying process as shown in Table . Cruz et al ., stated that the use of US pre‐dehydration prior to drying of grapes and plums increases drying rate, and drying kinetics as well as improves the physical properties and the general quality aspects of the final products.…”
Section: Emerging and Innovative Ntp Technologymentioning
confidence: 97%
“…Several works have been done to assess the influence of US pretreatment preceding drying on the physicochemical properties and microstructural alterations of various products. One of the important physical parameters of dehydrated product that enhance consumer acceptance and ensure microbiological stability is the total colour change and water activity respectively . Kroehnke et al ., studied the influence of US pretreatment on convective drying of potato and reported that the total colour change of dried potato significantly decreased when US was applied.…”
Section: Emerging and Innovative Ntp Technologymentioning
confidence: 99%